Alcohol consumption and reproductive toxicity: The role of in situ metabolism of ethanol in target organs - Castro, Jose Alberto (2014)
Epidemiological studies conducted in different countries showed that alcohol abuse in the youth and the adolescent is a problem of growing interest and relevance. Consequently, it can be envisaged that the number of adult drinkers is going to increase in the years to come. The detrimental effect of alcohol consumption on the health of young people is particularly serious when one considers that, with respect to reproductive health, this is the age range more relevant in both sexes. In women, reproductive health is not a minor issue, considering the alarming increase in drinking at an age directly related to the fertility window. It is important to note that due to differences in the metabolism of ethanol, women, compared with men, is facing an increased risk of negative consequences associated with the consumption of large amounts of alcohol. Harmful consequences of alcohol abuse have been reported in women such as a significant risk of infertility and an increased risk for endometriosis. Other studies concluded that the probability of a successful pregnancy decreased with the increase in the consumption of alcohol. For men, a large number of epidemiological studies evidenced that excessive alcohol consumption is associated with impaired testosterone production and testicular atrophy. Reproductive disorders caused by drinking should certainly involve alterations in critical hormonal factors controlling reproductive functions but also related to the direct toxic action of ethanol and its metabolites in the organs that constitute the reproductive systems of both sexes.